Aktivitas Antibakteri Ekstrak Etanol Daun Mangrove (Avecennia Marine) dari Perairan Pentadu Teluk Tomini Provinsi Gorontalo - Kaplale, Ahmad Soleh; Naiu, Asri Silvana; Yusuf, Nikmawatisusanti (Jambura Fish Processing Journal, 2026)
This study aims to isolate and identify triterpenoid compounds from the ethanol extract of mangrove leaves (Avicennia marina) and evaluate their antibacterial activity. The research employed both qualitative and quantitative methods. Qualitative analysis was conducted using thin-layer chromatography (TLC) with various eluents to detect the presence of triterpenoids, while quantitative analysis measured extract yield, retention factor (Rf), triterpenoid content via spectrophotometry, and antibacterial activity through the agar diffusion method. The best eluent for compound separation was a mixture of n-hexane and ethyl acetate (7:3). Ethanol extraction produced a yield of 14.8%, with the highest Rf value at 0.97. The highest triterpenoid concentration was 1.871905 ppm. Antibacterial tests showed an inhibition zone of approximately 6 mm, indicating moderate antibacterial activity. These results suggest that ethanol extract of A. marina leaves contains triterpenoid compounds with potential as antibacterial agents. This study opens opportunities for further development of A. marina-derived triterpenoids in antimicrobial formulations.